World Trade Union Conference, London 1945 (page 1) (1945)
1945 1945-1960 "World Trade Union Conference, London 1945 (page 1)" [T0458.jpg], 1945 This conference was convened by the TUC at County Hall, London (headquarters of the London County Council) 6-17 February, 1945. 204 representatives from 63 Unions around the world attended. Greetings from the Prime Minister, Winston Churchill, were conveyed by his deputy, Clement Attlee and King George VI gave an audience to a delegation from the conference.